The contribution of direct TLR signaling to T cell responses - Rahman, Adeeb H. (Immunol Res, 2009)
It is well established that Toll-like receptors (TLRs) play a critical role in the generation of innate immune responses and thereby also play an important, indirect role in the initiation of subsequent adaptive T cell responses. However, T cells also express certain TLRs, and we have focused on the physiological importance of direct TLR signaling in T cells. TLRs can function as co-stimulatory receptors that complement TCR-induced signals to enhance effector T cell proliferation, survival and cytokine production. We also found that TLR signaling pathways in T cells are required for the effective clonal expansion of antigen-specific T cells during infection in vivo. Thus, the importance of TLRs in T cell-mediated immunity reflects both T cell-extrinsic and T cell-intrinsic components, which warrants a reconsideration of the dogma that restricts germ-line encoded pattern recognition to cells of the innate immune system.